Gen Z's Perception of Green Open Space in Cirebon City - Dipta Bagaskara Leonan; Arni Muslimah Handayani Widjaja (Riviera Publishing, 2026)
Generation Z (Gen Z) possesses significant creative potential that requires supportive public spaces for discussion and collaboration; however, the availability of suitable open spaces in Cirebon City remains limited. This gap highlights the need to optimize existing Green Open Spaces (GOS) so that they can be transformed into creative public spaces for younger generations without requiring the construction of new infrastructure. This study aimed to examine Gen Z’s perceptions of the availability of green open spaces in Cirebon City and analyze the characteristics of ideal green open spaces based on their preferences. This study employed a descriptive statistical method with a quantitative approach. Data were collected through questionnaires administered to at least 100 Gen Z respondents aged 18–29 years across five subdistricts in Cirebon City using purposive sampling. The findings revealed that the highest perceived importance in the ecological aspect was visual/aesthetic vegetation (86%); in the social aspect, pedestrian accessibility; in the economic aspect, the provision of spaces for small and medium enterprises (SMEs) (78%); and in the visual aspect, well-maintained and clean parks (81%). The evaluation of current conditions indicated that public open spaces were adequate in terms of vegetation and basic facilities; however, significant gaps remained, particularly regarding hydrological functions for flood mitigation and environmental safety systems. As the primary recommendation, the development of public open spaces in Cirebon City should adopt the Smart & Sustainable Eco-park concept to integrate sustainable environmental elements and smart technologies, thereby accommodating Gen Z’s need for safe, well-maintained, and productive public spaces.